REKONSTRUKSI TEORI MASLAHAH DALAM KAJIAN PEMBAHARUAN PERUNDANGAN ISLAM: ANALISIS TERHADAP PEMIKIRAN NAJM AL-DIN AL-TUFI - Rajab, Khairunnas; Efrinaldi, Efrinaldi (Jurnal Syariah, 2009)
The meaning of maslahah is a fine or a profit. Theoretically, this mean that its important to study the context of maslahah to understand its benefits for people. Shariah law is required to guide the meaning of maslahah in our life. Maslahah encompasses both the aspect of living in the world and the here after. It is not merely on mental consideration in evaluating the good and bad, but rather based on rational Shariah law.